Integration of revelation and human knowledge - Ashimi, Tijani Ahmad (2017)
Human knowledge and revelation are precious gift of Allah to mankind. They are considered as reliable sources of different knowledge. In fact, revelation at least in its Islamic form seeks its justification in empirical reality; it sees empirical reality as manifestation of a transcendental reality. Therefore, human is linked to the truth of God either through revelation or reason. Yet, in this twenty first century, it is undeniable fact that, human reason which is the main source of human knowledge has gained momentum in some worldviews, on the ground that, human intellect is able to guide people to some extent to the broadest universal truths (such as existence of God), and it has also contributed immensely to the scientific development and technological advancement. As such, various disciplines of knowledge have been discovered by the virtue of human reason. However, it is worthwhile to remember that, this unique faculty of thinking that bestowed by Almighty Allah to human being (intellect) may not be able sometimes to provide insight of metaphysical worlds, such as hell, heaven, creation and eschatology etc... in details. Hence, the role of revelation is emerged to remedy such deficiency that can not be solved by human intellect alone. Thus, it is inadequate to reject revelation and contrast science with revealed knowledge. i.e the reality should not be confined exclusively to the realm of visible world and scientific empirical phenomena, under the raison d’etre that human reason can not ascertain transcendental reality. As a matter of fact, in Islam, both reveled knowledge and human acquired knowledge can work together for the sake of better understanding of this universe, and for the betterment of humanity at large. Based on this fact, this humble book will comprise of various chapters provided in the course outline; the book will adopt textual methodology, and relies on various books written by very reliable scholar, materials and references collected from various libraries. Finally, the book will highlight the possibility of integration of human acquired knowledge and reveled knowledge, and that will be followed by some suggestions and recommendations.